'Weakest Link' as a Cognitive Vulnerability Within the Hopelessness Theory of Depression in Chinese University Students. (18th March 2014) - Xiao, Jing; Qiu, Yu; He, Yini; Cui, Lixia; Auerbach, Randy P.; McWhinnie, Chad M.; Yao, Shuqiao
Abstract: The current study tested the cognitive vulnerability–stress component of hopelessness theory using a 'weakest link' approach (e.g. an individual is as cognitively vulnerable to depression as his or her most depressogenic attributional style makes him or her) in a sample of Chinese university students. Participants included 520 students in Changsha. During an initial assessment, participants completed measures assessing weakest link, depressive symptoms and occurrence of negative events once a month for 6 months. Results from hierarchical linear modelling analyses showed that higher levels of weakest link scores were associated with greater increases in depressive symptoms following the occurrence of negative events. Higher weakest link level was associated with greater increases in depressive symptoms over time. These results provide support for the applicability of the 'weakest link' approach to the hopelessness theory to Chinese university students. Copyright © 2014 John Wiley & Sons, Ltd.